A Semantical Analysis of Mappadendang in Wajo, South Sulawesi - Rusdiah Salam; Besse Rianti; Atma Putri (Fakultas Sastra - Universitas Muslim Indonesia, 2016)
The research aimed to find out the meaning of dancer movements in tradition of Mappadendang in Wajo, South Sulawesi. Mappadendang is one of tradition after harverst as gratitude to God. Mappdendang perform by 4 women and 3 men that pounding the rice. When the dancer pounding the rice by using pestle (alu) and mortar (palungeng). The result of punding the rice sounds “dendang”. That sounds called for Buginese tribe is mappadendang. In this research, the writer used a descriptive qualitative method to found and analyzed data. The writer analyzed and observed the location and interviewed some informants who can and able perform tradition of mappadendang, in Wajo, South Sulawesi, and also used some tools which has related with the research. The meaning of dancer movements in mappadendang has there are many meaning. Inside of dancer movement we can found the spiritual meaning, the meaning of sense, social meaning and entertainment meaning. The main movement in this tradition is expression gratitude to God. It describe for the believe’s society in Wajo always preserve their tradition to got blessed from God. The main purpose of mappadendang for the society has been given many positive impacts such us keep the relationship between society of Wajo, the event to looking for a partner and increase the result of harverst. Those impacts made the society of Wajo always perform this tradition.